Effects of microwave energy on grain quality of four Spanish rice varieties - Marzal, A.=700 1 Osca, J.M.; Castell, V.; Martinez, J.; Benedito, C.; Balbastre, J.V.; Sanchez Hernandez; D.
(Es, En)
ilus., 28 ref.
Keywords: ORYZA SATIVA; CONTROL DE PLAGAS; RADIACION; MICROONDAS; CALIDAD; GRANOS; ALMACENAMIENTO; ESPAÑA